Chemistry of the Antarctic stratosphere - Mcelroy, Michael B.; Salawitch, Ross J.; Wofsy, Steven C. (1988)
Interferometric measurements of HCl, ClNO3, HNO3, NO2, and NO obtained over the Antarctic in 1986 are used to model the chemistry of the atmosphere in the region of the Ozone Hole. The low abundance noted in stratospheric HCl is attributed to incorporation of HCl in polar stratospheric clouds and subsequent reaction of HCl with ClNO3. The results point to a net loss of HNO3 from the stratosphere and to the suppression of the abundance of odd nitrogen at high altitudes in the vortex. O3 loss is suggested to be due to the catalytic influence of halogen radicals.